Schwa and the loi de position in Southern French. Issue 2 (July 2014) - EYCHENNE, JULIEN
ABSTRACT This paper investigates the alternation of mid-open and mid-close vowels in southern French, a pattern known as the loi de position, and its relation to schwa. I offer a critical survey of the main analyses that have been put forward in the literature, showing how different conceptions of schwa influence the interpretation of the loi de position. I demonstrate that even in varieties where the pattern is considered fully productive, there are a number of exceptional cases that lend themselves to a usage-based approach. I develop an analysis of the phenomenon in the framework of Cognitive Grammar: the loi de position is formalized as the result of the interplay between substantive and symbolic constructions which emerge through usage.